2022
DOI: 10.7759/cureus.30555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on Pregnant Women and Newborns: A Review

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus originated in Wuhan, China, and spread all over the world, causing the worst pandemic of the century. The disease has a broad continuum of clinical presentations, from mild to life-threatening. The virus is highly contagious and transmittable to humans. Emerging evidence of its effects on pregnant women and newborns is inconsistent and ever-evolving. Therefore, the objective of this review is to compile the scientific literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…COVID-19 was declared a pandemic in March 2020 and has infected millions of people worldwide [1,2]. The disease manifested a wide range of clinical symptoms involving several organ systems [3][4][5][6]. The liver is the second most commonly affected organ in COVID-19, following the lungs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 was declared a pandemic in March 2020 and has infected millions of people worldwide [1,2]. The disease manifested a wide range of clinical symptoms involving several organ systems [3][4][5][6]. The liver is the second most commonly affected organ in COVID-19, following the lungs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Roles for maternal age and COVID-19 severity in disease presentation and outcome of SARS-CoV-2 infected neonates is hotly disputed ( 1 , 3 , 32 , 33 ). Discordance is exemplified by 3 recent reviews that found a lack of “concrete” evidence for vertical transmission or adverse effects of SARS-CoV-2 infection on pregnancy or newborns ( 32 , 34 , 35 ). Such discordance may be explained at least in part by an overriding majority of mildly symptomatic cases that differ only marginally from common complications of non-COVID pregnancies, and cases that were readily resolved by intensive care and anti-inflammation and/or antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this recognition, common treatment guidelines fail to address possible treatment models that include addressing the lifestyle and nutritional status of patients [9,10]. Compounding patterns of genetic disposition, sedentary living, adverse emotional states, ingestion of pro-inflammatory foods and chemicals, and deficiencies of key nutrients present as a driver of decreased health span and increased susceptibility to a vast majority of illnesses, including post-COVID syndrome [11][12][13]. Promoting general health through supporting the required intakes of the body should not fail to be a model of standard care for patients [14,15].…”
Section: Introductionmentioning
confidence: 99%